How Effective is Chemoembolization (TACE) Compared to Standard Care on The Survival of Hepatoma Patients? A Systematic Review - Haekal Mahargias; Febrina Mayasari Gunawan; Mutiara Amalia (International Medical Journal Corp. Ltd, 2026)
Introduction: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related mortality worldwide. Transarterial chemoembolization (TACE) is a standard treatment for intermediate-stage HCC, but its effectiveness compared to evolving standard care modalities requires continuous evaluation. This systematic review aims to synthesize current evidence on the effectiveness of TACE versus standard care on the survival of hepatoma patients. Methods: A systematic review was conducted by screening a pre-defined set of literature. Studies were included if they compared TACE (as a primary treatment) to any form of standard care (e.g., supportive care, systemic therapy, other locoregional treatments) in HCC patients and reported survival outcomes. Data on study characteristics, patient populations, interventions, and outcomes (overall survival, progression-free survival, safety) were extracted and synthesized narratively. Results: The review included 200 studies, encompassing RCTs, meta-analyses, and cohort studies. TACE consistently demonstrated a significant survival benefit over best supportive care, with median overall survival extended from 3-7 months to 20-31 months in some studies (Biselli et al., 2005; Yuen et al., 2003). Compared to systemic monotherapy like sorafenib in advanced stages, TACE showed at least comparable outcomes (Pinter et al., 2012). While conventional TACE (cTACE) and drug-eluting bead TACE (DEB-TACE) showed mixed survival results, DEB-TACE was often associated with a better safety profile (Bzeizi et al., 2021; Chen et al., 2017). The most significant advancement was seen with combination therapies; TACE plus tyrosine kinase inhibitors and immunotherapies (e.g., LEAP-012, EMERALD-1) markedly improved progression-free survival (HR 0.66-0.77) compared to TACE alone (Kudo et al., 2025; Lencioni et al., 2024). Discussion: The evidence confirms TACE's role as a cornerstone of HCC treatment, particularly for intermediate-stage disease. Its effectiveness is maximized in patients with preserved liver function (Child-Pugh A) and low tumor burden. The field is shifting towards combination strategies, which offer superior tumor control but require careful management of increased toxicity. Major limitations include high heterogeneity in TACE protocols and control arm definitions across studies. Conclusion: TACE significantly improves survival compared to supportive care and remains a vital treatment for HCC. Emerging evidence strongly supports combining TACE with systemic therapies to enhance outcomes, establishing a new standard for many patients. Future research should focus on optimizing patient selection for these combination approaches.